(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
ANNOTATSIYA: Ushbu maqolada atmosfera yeming himoya qatlami bo‘lib, tirik organizmlarni quyoshdan keladigan ultrabinafsha nurlardan, koinotdan tushadigan meteoritlaming ta’siridan asrashi, atmosfera yer sathining issiqlik tartibini bir maromda saqlashi, mabodo atmosfera bo’lmaganda edi,unda yerda kechqurun - 100 °C sovuq, kunduzi +100 °C issiq bo‘lishi kabi jarayonlar ko’rib chiqiladi.Bundan tashqari ushbu maqolada yerda hayot mavjudligining asosiy sharti atmosfera havosining ANNOTATION: This article discusses the processes that the atmosphere is a protective layer of the earth, protecting living organisms from ultraviolet rays from the sun and meteorites from space, maintaining a uniform temperature regime on the earth’s surface, and if there were no atmosphere, it would be -100 °C cold at night and +100 °C hot during the day. In addition, this article discusses the main condition for the existence of life on Earth, such as the presence of atmospheric air, the fact that the atmosphere has a clear layered structure and the lower layer is called the troposphere, its height is 10-15 km depending on the latitude of the Earth, this layer constitutes 80% of the mass of the atmosphere and about 80% of the water vapor, and the development of physical processes that form the climate and weather in different regions of our planet. АННОТАЦИЯ: В данной статье рассматриваются процессы, происходящие в атмосфере как защитном слое Земли, оберегающем живые организмы от ультрафиолетовых лучей Солнца и метеоритов из космоса, поддерживающем равномерный температурный режим на поверхности Земли. Если бы атмосферы не было, ночью было бы -100 °C, а днем ​​+100 °C. Кроме того, в статье обсуждаются основные условия существования жизни на Земле, такие как наличие атмосферного воздуха, четкая слоистая структура атмосферы, нижний слой которой называется тропосферой (ее высота составляет 10-15 км в зависимости от широты Земли, этот слой составляет 80% массы атмосферы и около 80% водяного пара), а также развитие физических процессов, формирующих климат и погоду в различных регионах нашей планеты.